The suspended sediment yield and provenance of the Inxu River Catchment, Eastern Cape - Nyamela, Namso (Rhodes University, Faculty of Science, Department of Geography, 2019)
The excessive deposition and accumulation of suspended sediment leads to the degradation of water resources such as dams and rivers. For the purpose of preserving and protecting these resources, suspended sediment needs to be managed, and its management should be catchment-wide and catchment-specific. This is certainly the case for the eroded Inxu River Catchment, which has been identified as a major contributor of sediment to the planned Lalini Dam on the Tsitsa River (a tributary of the Mzimvubu River). Knowledge of suspended sediment flux and catchment sources will aid the design of relevant strategies to manage suspended sediment production. Suspended sediment flux was determined from sediment samples that were collected using citizen-based monitoring techniques at calendar- and event-based sampling frequency, along with discharges estimated using stage-discharge relationships. Sediment source areas were identified by determining the suspended sediment contribution from major sub-catchments and observing similarities in the characteristics of the sub-catchments that produced the most sediment. The Inxu River Catchment produced 5.5 t/ha/yr between 01 May 2016 and 30 April 2017. When compared to modelled sediment yield (7 t/ha/yr) from Le Roux et al. (2015), modelled output was not far off from the measured results and both measured and modelled results identified similar sediment source areas. Q-SSC relationships observed at the Inxu River Outlet indicated that sediment was eroded from local areas and sub-catchment sediment contribution confirmed that most of the sediment was from the lower Inxu River Catchment. Within this area, the Ncolosi and Qwakele River Sub-catchments were major sediment source areas and were subject to widespread gully erosion. Gully erosion was prominent on gentle slopes, foot slopes and valley-bottoms that have concave slope curvature and lie on the Tarkastad Formation. This Formation is associated with some of the most dispersive soils in the area. Moreover, the catchment is vulnerable to erosion due to cultivation and subsequent land abandonment, continuous grazing and dense rural populations. Other studies in the Mzimvubu catchment identified similar catchment characteristics that contribute to excessive erosion. This study has successfully measured sediment yield and identified areas that should be targeted and prioritised for rehabilitation within the Inxu River Catchment. The findings could be applied to a wider catchment scale. The study has successfully demonstrated the use of citizen-based monitoring and desktop techniques and has also identified some pitfalls of this approach.
Keywords: Suspended sediments -- South Africa -- Inxu River; Sedimentation and deposition -- South Africa -- Inxu River; Watershed management -- South Africa -- Inxu River; Erosion -- South Africa -- Inxu River; Soil erosion -- South Africa -- Inxu River